The Comedy of Maine’s Commons: Private Ownership as Economic Development - Cianchette, Michael (Maine Policy Review, 2020)
In Maine, we have managed to avoid the tragedy of the commons in several arenas. One way we have supplanted tragedy with comedy is through supporting and respecting private ownership of property. Some of this support is by necessity, as areas that might be publicly owned in other states—such as our expansive forests—are predominately privately owned in Maine. Other times, it is through a recognition that the private sector supports responsible public investment and is willing to financially support it through increased tax revenue. As Maine prepares for its next 200 years, policymakers should take heed of these examples. Government involvement can be supportive rather than adversarial. And when Mainers and Maine businesses are empowered to manage their own affairs, great things happen.